The efficacy and safety of mannitol challenge in a workplace setting for assessing asthma prevalence. (2nd December 2018) - de Menezes, Marcelo B.; Ferraz, Erica; Brannan, John D.; Martinez, Edson Z.; Vianna, Elcio O.
ABSTRACT: Objective : There is no standard definition of asthma for epidemiological purposes; most surveys use symptoms and bronchial hyperresponsiveness. Few studies tested mannitol challenge test (MCT) in occupational settings. We sought to determine efficacy and safety of MCT in detecting subjects with asthma symptoms in the workplace. Methods : In this cross-sectional study we recruited 908 workers in 2 universities; they underwent a respiratory questionnaire, spirometry, skin prick tests, and MCT. Results : Eight hundred and eleven subjects completed the study; 11.1% had a positive MCT; 8.14% had asthma. MCT had low sensitivity (35.4–61.9%) but high specificity (90.2–94.9%) to detect symptomatic individuals. The most prevalent symptom was wheezing in the last 12 months. Twenty-four of those with a positive MCT (26.7%) had no positive replies to the questions on asthma symptoms. Among subjects with a positive MCT, 71.9% achieved 95% of baseline FEV1 after 15 minutes of salbutamol recovery treatment. Nine subjects (1.1%) had adverse events that prevented the test from being completed. Conclusions : MCT has high specificity but low sensitivity to detect symptomatic subjects in the workplace. It may detect subjects with hyperresponsiveness but no symptoms, who could be at risk of developing airway diseases. The test is safe and well tolerated.